The Pattern Instance Notation: A Simple Hierarchical Visual Notation for the Dynamic Visualization and Comprehension of Software Patterns - Smith, Jason (Electronic Communications of the EASST, 2010)
Design patterns are a common tool for developers and architects to understand and reason about a software system. Visualization techniques for patterns have tended to be either highly theoretical in nature, or based on a structural view of a system’s implementation. The Pattern Instance Notation is a simple visualization technique for design patterns and other abstractions of software engineering suitable for the programmer or designer without a theoretical background. While based on a formal representation of design patterns, using PIN as a tool for comprehension or reasoning requires no formal training or study. PIN is hierarchical in nature, and compactly encapsulates abstractions that may be spread widely across a system in a concise graphical format, while allowing for repeated unveiling of deeper layers of complexity and interaction on demand. It is designed to be used in either a dynamic visualization tool, or as a static representation for documentation and as a teaching aid.